Effect of gamma irradiation on space charge and charge trap characteristics of epoxy–MgO nanocomposites. (20th November 2019) - Guvvala, Nagaraju; Nageshwar Rao, Burjupati; Sarathi, Ramanujam
Abstract : Insulating materials used in power apparatus required to be space charge free. Epoxy–magnesium oxide (MgO) nanocomposites were prepared and gamma rays were irradiated for different dosages to understand the dielectric parameters variation, space charge characteristics, surface potential variations, and for getting charge trap characteristics of the material. It is realised that permittivity increases and then reduces when the irradiation level is increased. Tan (δ) marginally increased with increasing dosage of gamma irradiation. Space charge accumulation reduces with increase in wt% of MgO in epoxy resin. 3 and 5 wt% MgO added samples showed stable space charge accumulation and fast decay during depoling, irrespective of irradiation level. Surface potential decay time reduces with irradiated specimens. After irradiation, epoxy nanocomposites showed both shallow trap formation and deep trap formation and found that shallow trap density is high compared to the deep trap density. All the irradiated specimens showed a decrease in the trap energy level compared to the virgin specimens.